Counterfeit proneness: Conceptualisation and scale development - Sharma, Piyush; Chan, R.Y. (Routledge, 2011)
Counterfeiting is one of the fastest-growing industries in the world across a wide range of product categories, including music, movies, food, computer software, pharmaceuticals, fertilisers, and machinery parts. Prior research focuses on deceptive counterfeiting in which the consumers are not aware about buying counterfeit products, with little attention to non-deceptive counterfeiting in which consumers knowingly purchase counterfeit products. Most of this research is fragmented and exploratory in nature, resulting in mixed or inconclusive findings that leave many important questions unanswered. For example, it is still not clear why some customers are more prone to buying counterfeit products compared to others. We address this important gap by conceptualising counterfeit proneness (CFP), an individual-level psychological trait that relates closely with counterfeit purchase behaviour. We also develop a scale to measure this trait and validate itthrough a series of empirical studies. Finally, we discuss some limitations of our approach and directions for future research.